Changing the Business Model: Effects of Venture Capital Firms and Outside CEOs on Portfolio Company Performance. (8th December 2014) - Gerasymenko, Violetta; De Clercq, Dirk; Sapienza, Harry J.
<x xml:space="preserve">Abstract</x> This study extends extant research on business model change by examining the impact of venture capital firms (VCFs) on the performance of young ventures that have substantially changed their business model. The analysis, using a unique dataset of 163 venture capital‐backed portfolio companies (PFCs), reveals a positive relationship between the scope of VCF involvement and PFC performance. Furthermore, the VCFs' experience with business model change and the recruitment of an outside CEO to the PFC both increase the positive impact of VCF involvement. These findings have implications for theory and practice. Copyright © 2014 Strategic Management Society.